2017
DOI: 10.1159/000480344
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Blue Light Emitting Diode Irradiation On the Proliferation, Apoptosis and Differentiation of Bone Marrow-Derived Mesenchymal Stem Cells

Abstract: Background/Aims: Blue light emitting diodes (LEDs) have been proven to affect the growth of several types of cells. The effects of blue LEDs have not been tested on bone marrowderived mesenchymal stem cells (BMSCs), which are important for cell-based therapy in various medical fields. Therefore, the aim of this study was to determine the effects of blue LED on the proliferation, apoptosis and osteogenic differentiation of BMSCs. Methods: BMSCs were irradiated with a blue LED light at 470 nm for 1 min, 5 min, 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 41 publications
1
28
0
Order By: Relevance
“…Many in vivo and in vitro studies generally use doses of 2 Gy for experimentation [25, 27]. The present study found that 2 Gy radiation could clearly inhibit cell proliferation, which was similar to the observations of previous studies [2526]. Radiation-induced cell damage arises due to the energy deposited directly onto DNA and the induction of ROS, which cause DNA breakage in the nucleus and affect cell cycle checkpoints.…”
Section: Discussion/conclusionsupporting
confidence: 90%
See 1 more Smart Citation
“…Many in vivo and in vitro studies generally use doses of 2 Gy for experimentation [25, 27]. The present study found that 2 Gy radiation could clearly inhibit cell proliferation, which was similar to the observations of previous studies [2526]. Radiation-induced cell damage arises due to the energy deposited directly onto DNA and the induction of ROS, which cause DNA breakage in the nucleus and affect cell cycle checkpoints.…”
Section: Discussion/conclusionsupporting
confidence: 90%
“…Reactive oxygen species (ROS), produced by the radiolysis of water, activate the transcription factor nuclear factor kappa-B, in turn enhancing the expression of p16INK4A. The expression of p16INK4A protein activates the pRb tumor suppressor protein, thereby suppressing the expression of certain genes involved in cell proliferation, ultimately leading to durable cell-cycle arrest triggering mutagenesis, DNA damage, apoptosis, and nucleotide excision repair, causing an inflammatory response and the expression of inflammatory factors [2627, 42, 50]. These post-radiation effects can lead to osteopenia, radiation-induced osteoporosis, and a higher risk of serious fractures [78].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have indicated that increased ROS production resulted in DNA damage [20]. We thus examined whether iron overload causes DNA damage in hiPSCs and hESCs.…”
Section: Resultsmentioning
confidence: 99%
“…Intracellular ROS production plays important roles in the proliferation and apoptosis of various cell types. It has been reported that ROS production regulates aging, senescence, and osteogenic differentiation in BMSCs [ 20 22 ]. To further evaluate the effects of the EGB or EGB CS against ROS production in H 2 O 2 -induced BMSCs, we performed DCFH-DA staining assay.…”
Section: Resultsmentioning
confidence: 99%